9d-2d+6d-6=6d

Simple and best practice solution for 9d-2d+6d-6=6d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9d-2d+6d-6=6d equation:


Simplifying
9d + -2d + 6d + -6 = 6d

Reorder the terms:
-6 + 9d + -2d + 6d = 6d

Combine like terms: 9d + -2d = 7d
-6 + 7d + 6d = 6d

Combine like terms: 7d + 6d = 13d
-6 + 13d = 6d

Solving
-6 + 13d = 6d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-6d' to each side of the equation.
-6 + 13d + -6d = 6d + -6d

Combine like terms: 13d + -6d = 7d
-6 + 7d = 6d + -6d

Combine like terms: 6d + -6d = 0
-6 + 7d = 0

Add '6' to each side of the equation.
-6 + 6 + 7d = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 7d = 0 + 6
7d = 0 + 6

Combine like terms: 0 + 6 = 6
7d = 6

Divide each side by '7'.
d = 0.8571428571

Simplifying
d = 0.8571428571

See similar equations:

| y/8=2/10 | | (3+5x^2)(3-5x^2)= | | 3x^3-7x^2=10 | | 9x-7=6x+16 | | (2x+3)2-3x-4=0 | | 16a^3b+4ab=0 | | 6+9+6= | | 12X^3+3X^2-24X^2-6X=0 | | (x+2)(x+8)=72 | | 5s+12=0 | | (3d^4-4d^3+6)(-3c^2d)= | | 12X^3+3X^2-24X-6X=0 | | -x^2+5x=3 | | (3d^4-4d^3+6)(-3cd)= | | 4(6X-5)2= | | 6d+3d-5d-8=2d | | 9n=8n+24 | | 3x-9=2x+15 | | 5(3x-2)5= | | 3n+10=70 | | 12n-3=9 | | 76-7x=38x+21 | | (3x-4)(x-4)(x+5)= | | 3n+6=3n | | 78100-781000= | | x^2+6x-112=0 | | 14x+2y= | | (9x^2-7x+8)(8x^2+9x-7)= | | 15w-14w+12=10w | | 9x+12=3x-6 | | 58-5x=4x+17 | | 14-b=19 |

Equations solver categories